Comprehensive metabolomics analysis based on UPLC-Q/TOF-MSE and the anti-COPD effect of different parts of Celastrus orbiculatus Thunb. Issue 14 (26th February 2020) - Yang, Na; Wang, Han; Lin, Hongqiang; Liu, Junli; Zhou, Baisong; Chen, Xiaoling; Wang, Cuizhu; Liu, Jinping; Li, Pingya
Abstract : The root, stem and leaf of Celastrus orbiculatus Thunb. (COT) have all been used as Chinese folk medicine. Abstract : The root, stem and leaf of Celastrus orbiculatus Thunb. (COT) have all been used as Chinese folk medicine. Aiming at revealing the secondary metabolites and screening the anti-COPD effect of COT, the comprehensive phytochemical and bioassay studies were performed. Based on the ultra-high performance liquid chromatography combined with quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF-MS E ), the screening analysis of components in COT was conducted with the UNIFI platform, the metabolomics of the three parts were analyzed with multivariate statistical analysis. Cigarette smoke extract (CSE)-stimulated inflammatory model in A549 cells was used to investigate the biological effect of the three parts. A total of 120 compounds were identified or tentatively characterized from COT. Metabolomics analysis showed that the three parts of COT were differentiated, and there were 13, 8 and 5 potential chemical markers discovered from root, stem and leaf, respectively. Five robust chemical markers with high responses could be used for further quality control in different parts of COT. The root, stem and leaf of COT could evidently reduce the levels of pro-inflammatory factors in a dose-dependent way within a certain concentration range. The stem part had a stronger anti-COPD effect than root and leaf parts. This study clarified the structural diversity of secondary metabolites and the various patterns in different parts of COT, and provided a theoretical basis for further utilization and development of COT.